2021
DOI: 10.1002/jctb.6900
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic co‐digestion of food waste and microalgae in an integrated treatment plant

Abstract: BACKGROUND Anaerobic co‐digestion has been considered for improving anaerobic digesters’ stability and methane production, particularly for residues with low biodegradability or lack of alkalinity. Food waste was identified as a biomass with macro and micronutrients unbalance and low alkalinity content, both of which hamper its anaerobic digestion. The present study focused on evaluating the anaerobic co‐digestion of food waste and microalgal biomass harvested from an open pond treating food waste digestate. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…These changes led to a decrease in the acidity of the environment, leading to an increase in the activity of methanogenic bacteria, which in turn allowed biogas production to be higher by 258.16 mL•g −1 VS and by 359.74 mL•g −1 VS, compared to the mono-digestion of FW and WH. Ferreira et al (2021) showed that a mixture of food waste and microalgae (MA) increased methane yields, compared to the separate digestion of FW and MA, by 21% and 55%, respectively [103]. Based on the results, it was concluded that the increase in the production of the gas in question was due to an increase in the buffer capacity of the ferment in the digester and a decrease in the accumulation of organic acids through the addition of microalgae.…”
Section: Co-digestion Of Food Waste With Plants Plant Residues and Algaementioning
confidence: 99%
“…These changes led to a decrease in the acidity of the environment, leading to an increase in the activity of methanogenic bacteria, which in turn allowed biogas production to be higher by 258.16 mL•g −1 VS and by 359.74 mL•g −1 VS, compared to the mono-digestion of FW and WH. Ferreira et al (2021) showed that a mixture of food waste and microalgae (MA) increased methane yields, compared to the separate digestion of FW and MA, by 21% and 55%, respectively [103]. Based on the results, it was concluded that the increase in the production of the gas in question was due to an increase in the buffer capacity of the ferment in the digester and a decrease in the accumulation of organic acids through the addition of microalgae.…”
Section: Co-digestion Of Food Waste With Plants Plant Residues and Algaementioning
confidence: 99%
“…Co-digestion of two or more substrates has a beneficial effect on increasing biogas production yield by up to 200% and improving the stability of the anaerobic digestion process [57]. Ferreira et al [58] achieved the highest methane yield using a mixture of 75% food waste and 25% microalgae. This resulted in a methane yield of 514 mL/gVS and a synergy between the substrates that was 28% higher than the theoretical value.…”
Section: Anaerobic Fermentation Of Microalgal Residuesmentioning
confidence: 99%
“…Microalgae aid in removing organic pollutants from wastewater, demonstrating promise in waste management and water quality improvement (Mulbry et al, 2008). Additionally, the integration of microalgae cultivation with waste anaerobic digestion enhances system stability and methane production, highlighting the potential for sustainable waste treatment and biomass generation (Ferreira et al, 2022).…”
Section: Enhancing Water Quality and Waste Management: Synergizing Bi...mentioning
confidence: 99%